2012
DOI: 10.1540/jsmr.48.137
|View full text |Cite
|
Sign up to set email alerts
|

Surface CD3 expression proceeds through both myosin regulatory light chain 9 (MYL9)-dependent and MYL9-independent pathways in Jurkat cells

Abstract: CD3 is a complex of polypeptides which form part of the T cell receptor. Normal human peripheral pan T cells, express not only CD3, but the mRNA for myosin regulatory light chains MYL9, MYL12A, and MYL12B are also significantly expressed. In the Jurkat wild strain, an acute T cell leukemia cell line, CD3 on the surface and MYL9 mRNA are not expressed, while both MYL12A mRNA and MYL12B mRNA are expressed. Jurkat-I, a new clone was established by the transfection of the MYL9 gene into the Jurkat wild strain. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A previous pharmacological study revealed that the inhibition of MLCK changed cell motility and wound contraction (22). There are three types of myosin regulatory light chains: MYL12B, MYL12A and MYL9 (23). The MYL9 gene is highly expressed in vascular smooth muscle cells (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous pharmacological study revealed that the inhibition of MLCK changed cell motility and wound contraction (22). There are three types of myosin regulatory light chains: MYL12B, MYL12A and MYL9 (23). The MYL9 gene is highly expressed in vascular smooth muscle cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…There are three types of myosin regulatory light chains: MYL12B, MYL12A and MYL9 (23). The MYL9 gene is highly expressed in vascular smooth muscle cells (23). It has been reported that MYL9 impacts cell motility and contractility, and that is an important component of the contractile apparatus of cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…In our X-gal analysis of tissues from Myl9 -/+ mice, β-galactosidase activity was only ever detected in α-SMA + cells and not in any non-smooth muscle cells. This was somewhat surprising given the reports of MYL9 expression in endothelial cells and various hematopoietic cells, such as T cells [8,9,11]. It is possible that X-gal staining may not be sensitive enough to detect low level Myl9 promoter activity.…”
Section: No Evidence For Significant Myl9 Expression In Hematopoietic...mentioning
confidence: 97%
“…Whether MYL9 is also required for non-muscle myosin stability isn't clear but it has been shown to exert a range of non-muscle functions. MYL9, as well as MYL12A and MYL12B, has been found in T cells where it has been shown to have a role in positioning CD3 to the cell surface [8]. CD3 is a critical protein complex required for transducing signals from the T cell receptor.…”
Section: Introductionmentioning
confidence: 99%